Growth and Characterization of Triglycine Sulphate Single Crystal by Sankaranaryanan–Ramasamy Method. (2018) - Sabarish, V.C. Bharath; Kumar, G. Ramesh; Raj, S. Gokul; Durairajan, A.; Rajashekar, B.N.
Abstract: Transparent single crystal of dimension 10 x 1 x 1 cm 3 has been successfully grown from Sankaranarayanan–Ramasamy (SR) method. The grown crystal was subjected to Optical Transmittance studies using UV-Vis-NIR spectrum. The presence of various functional groups and the vibrational structure of the compound was elucidated from Fourier transform infrared analysis. The other possible vibrations have also been identified through Raman stud